Laser induced Compton scattering to dark matter in effective field theory - Ma, Kai; Li, Tong (The journal of high energy physics, 2025)
A bstract The detection of light dark matter (DM) is a longstanding challenge in terrestrial experiments. High-intensity facilities with intense electromagnetic field may provide a plausible strategy to study strong-field particle physics and search for light DM. In this work, we propose to search for light DM particles through nonlinear Compton scattering in the presence of a high-intensity laser field. An ultra-relativistic electron beam collides with an intense laser pulse containing a number of optical photons and then decays to a pair of DM particles. We take into account the Dirac-type fermionic DM in a leptophilic scenario and the DM-electron interactions in the framework of effective field theory. The decay rates of an electron to a DM pair are calculated for effective DM operators of different bilinear products. We show the sensitivities of laser induced Compton scattering to the effective cutoff scale for DM lighter than 1 MeV and compare them with direct detection experiments.